The Application of New Automatic Weather Station in Power System - Jinhua Liu; Feilong Huang (Institute of Advanced Engineering and Science, 2013)
Aiming at special demanding of weather monitoring in power system, an application project was designed basing on new type distributed and smart automatic weather station (AWS) Defects such as fixed hardware configuration and centralized data acquisition are overcome in new AWS. With distributed data acquisition node, AWS can extend and add new sensors for disaster forecasting of lightning, strong gale, icing of transmission line and insulators contamination flashover in power system and it is also convenient for evaluation of wind energy, solar energy and for power load forecasting. Using protective power supply to each node, AWS has high performance of lightning protection, which will not let system breakdown for any node crash. Three-stage automatic self-checking for node state is included, which can make failure diagnosis efficient. Data quality checking node is created in new AWS. It can provide data self-checking function and improve reliability of data from unattended AWS. Finally, application models of monitoring data are introduced. New type AWS is fit for system with many sensors or large amount of data flow. And this project can supply accurate, adequate and real-time data for weather disaster prevention and other applications in power system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1990